A Subregular Bound on the Complexity of Lexical Quantifiers - Graf, Thomas (Proceedings of the Amsterdam Colloquium, 2019)
Semantic automata were developed to compare the complexity of generalized quantifiers in terms of the string languages that describe their truth conditions. An important point that has gone unnoticed so far is that these string languages are remarkably simple for most quantifiers, in particular those that can be realized by a single lexical item. Whereas complex quantifiers such as an even number of correspond to specific regular languages, the lexical quantifiers every, no, some as well as numerals do not reach this level of complexity. Instead, they all stay close to the bottom of the so-called subregular hierarchy. What more, the class of tier-based strictly local languages provides a remarkably tight characterization of the class of lexical quantifiers. A significant number of recent publications have also argued for the central role of tier-based strict locality in phonology, morphology and syntax. This suggests that subregularity in general and tier-based strict locality in particular may be a unifying property of natural language across all its submodules.